The effects of hesperidin supplementation on insulin resistance and sensitivity in adults: a systematic review and meta-analysis of randomized controlled trials - Li, Wen; Liu, Yuyin; Zhu, Kun; Wu, Lijiao; Liu, Meixi; Chen, Qiu (Frontiers in Nutrition, 2026)
This systematic review and meta-analysis of randomized controlled trials (RCTs) aimed to evaluate the effects of hesperidin supplementation on insulin resistance and sensitivity in adults. Two authors independently searched electronic databases, including PubMed, Scopus, Embase, Web of Science, and the Cochrane Library, from their inception to July 2025 for relevant RCTs. The quality of the included studies was assessed using the Cochrane Collaboration’s tool for assessing the risk of bias. Heterogeneity among the included studies was evaluated using Cochrane’s Q test and the I2 statistic. A meta-analysis of eligible studies was conducted using either fixed- or random-effects models, with the weighted mean difference (WMD) serving as the overall effect size. Pre-specified subgroup and sensitivity analyses were performed to explore potential sources of heterogeneity. This meta-analysis included 16 studies, comprising 845 participants and assessing five outcome measures. We found that hesperidin supplementation significantly reduced the homeostatic model assessment of insulin resistance (HOMA-IR) (WMD: −0.43, 95%CI: −0.82, −0.03; p = 0.034) and increased the quantitative insulin sensitivity check index (WMD: 0.05, 95%CI: 0.01, 0.08; p = 0.005). However, no significant effects were observed on insulin, fasting blood glucose, or glycated hemoglobin A1c. Subgroup analyses indicated that supplementation with high-dose, long-duration purified hesperidin, particularly in individuals with metabolic disorders and obesity, had a positive effect on insulin levels. However, subsequent trial sequential analysis revealed that hesperidin confers no statistically significant improvement in HOMA-IR. In conclusion, the current body of evidence does not support hesperidin as an effective intervention for ameliorating insulin resistance or enhancing glycemic control. Future investigations are warranted to explore its potential efficacy in specific populations or subgroups.Systematic review registrationPROSPERO, identifier (CRD420251102342).